Kemampuan Siswa Kelas IV Sekolah Dasar dalam Penggunaan Kata Depan - Sunarto Hapsoyo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was designed to describe the pupils' ability in using prepositions. Data were collected from 112 fourth graders of elementary schools in Sentul, Blitar Municipality, by observing and evaluating their compositions. The analysis was focused on describing the fequency and accuracy of the use of monomorphemic and polymorphemic prepositions. It was found out that 82.41 % of the pupils used the monomorphemic prepositions accurately, and 100 % of them used the polymorphemic prepositions accurately. The total accurate use was 85.48 %.